2015
DOI: 10.1155/2015/195093
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Sedation Improves Colonoscopy Quality Long-Term

Abstract: Background. Quality monitoring and improvement is prerequisite for efficient colonoscopy. Aim. To assess the effects of increased sedation administration on colonoscopy performance. Materials and Methods. During Era 1 we prospectively measured four colonoscopy quality indicators: sedation administration, colonoscopy completion rate, adenoma detection rate, and early complications rate in three cohorts: cohort A: intention for total colonoscopy cases; cohort B: cohort A excluding bowel obstruction cases; cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…ADR has previously been linked to patient factors such as age, race, gender, comorbidities, and procedural factors -most notably withdrawal time and even endoscopist personality [23][24][25][26] . In addition, studies have also analysed differences in the ADR between sedated and unsedated patients with some showing clear benefit for sedation 27 and others showing no difference 28,29 . Studies comparing ADRs in patients sedated with CS and MAC have demonstrated either no difference 30 or a benefit to CS over MAC 29 .…”
Section: Discussionmentioning
confidence: 99%
“…ADR has previously been linked to patient factors such as age, race, gender, comorbidities, and procedural factors -most notably withdrawal time and even endoscopist personality [23][24][25][26] . In addition, studies have also analysed differences in the ADR between sedated and unsedated patients with some showing clear benefit for sedation 27 and others showing no difference 28,29 . Studies comparing ADRs in patients sedated with CS and MAC have demonstrated either no difference 30 or a benefit to CS over MAC 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced when you consider the results of a study that demonstrated a larger amount of mono or dual (conscious) sedation improved many aspects of colonoscopy assurance measures. ADR increased (25.9 to 35 %), early complications rate decreased (3.4 to 0.3 %) and completion rates increased (88.3 to 96.4 %) [13]. When higher levels of sedation are used (using propofol), studies have suggested an increase in ADR; however, these also showed an increase in complication rates, particularly perforation [14].…”
Section: Use Of Antispasmodics and Sedationmentioning
confidence: 99%
“…Colonoscopy has been widely performed to screen colorectal diseases. Most of the procedures are performed under sedation and/or analgesia due to the discomfort or pain, [ 1 , 2 ] and adequate sedation may improve the quality of colonoscopy [ 3 , 4 ]. Sedation for endoscopy can be classified into minimal, moderate, and deep sedation, depending on the different types of procedures, and moderate sedation level is regarded as the minimal requirement for colonoscopy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%